Fiber-reinforced resin sheets, fiber-reinforced resin chopped materials, fiber-reinforced resin composite materials, and resin molded products

A fiber-reinforced resin sheet with ethylene-vinyl alcohol copolymer resin and controlled fiber volume and thickness addresses the challenge of achieving high strength and gas barrier, ensuring excellent molding properties and mechanical integrity for resin molded products.

JP7625552B2Active Publication Date: 2025-02-03FUKUBI KAGAKU IND
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022088777
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-02-03
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

Existing fiber-reinforced resin sheets using thermoplastic resin as a matrix face challenges in achieving both high strength and excellent gas barrier properties, particularly when using ethylene-vinyl alcohol copolymer resin, due to issues with thickness and volume content of reinforced fibers affecting molding processing and gas barrier performance.

Method used

A fiber-reinforced resin sheet with ethylene-vinyl alcohol copolymer resin film and reinforced fibers, where the volume content of fibers is between 20% and 70% and the thickness is between 20 μm and 80 μm, allowing for a balanced structure that enhances both gas barrier and strength while facilitating good molding processing.

Benefits of technology

The solution provides a fiber-reinforced resin sheet with excellent gas barrier, particularly for hydrogen gas, high tensile and bending strength, and improved molding flexibility, enabling the production of resin molded products with varied shapes and enhanced mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625552000002
    Figure 0007625552000002
  • Figure 0007625552000003
    Figure 0007625552000003
  • Figure 0007625552000001
    Figure 0007625552000001
Patent Text Reader

Abstract

To provide a fiber-reinforced resin sheet with which a fiber-reinforced resin composite material having excellent gas barrier property and high intensity can be obtained, and which has excellent moldability.SOLUTION: A fiber-reinforced resin sheet contains: an ethylene-vinyl alcohol copolymer resin film having a thickness of 10 μm or more and 50 μm or less; and a plurality of reinforced fibers laminated on the ethylene-vinyl alcohol copolymer resin film in a state in which fiber directions are oriented to an identical direction. A volume content Vf of the reinforced fibers is 20% or more and 70% or less and the thickness is 20 μm or more and 80 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced resin sheet containing an ethylene-vinyl alcohol copolymer resin film and reinforcing fibers. [Background technology]

[0002] Fiber-reinforced resin composites are widely used in a wide range of applications, from sports and leisure to industrial applications such as automobiles and aircraft. Fiber-reinforced resin composites are manufactured using an intermediate material, i.e., a prepreg (hereinafter also referred to as a "fiber-reinforced resin sheet"), in which a reinforcing material made of long fibers (continuous fibers) such as reinforcing fibers is impregnated into a resin matrix. Specifically, a fiber-reinforced resin composite or a resin molded product containing the same can be obtained by stacking multiple fiber-reinforced resin sheets and heating and curing them, or heating and cooling them to solidify them.

[0003] Conventionally, in the production of fiber-reinforced resin composites, thermosetting resins have been widely used as matrix resins because of their excellent strength and rigidity (see, for example, Patent Document 1). However, fiber-reinforced resin sheets using thermosetting resins have problems such as low impact resistance and difficulty in secondary processability and mass production. For this reason, in recent years, fiber-reinforced resin sheets in which reinforcement fibers are impregnated using thermoplastic resins as matrix resins have been widely developed. Such fiber-reinforced resin sheets are easy to melt by heating and solidify by cooling. For this reason, fiber-reinforced resin sheets using thermoplastic resins have excellent operability during molding processing, and are expected to have effects such as shortening the production time of fiber-reinforced resin composites or resin molded products containing them, and also lead to cost reduction.

[0004] On the other hand, as an example of the use of such a fiber-reinforced resin composite, a pressure-resistant container having a two-layer structure suitable for mounting on an automobile or the like is known. For example, Patent Document 2 describes a gas cylinder having an inner shell having gas barrier properties and an outer shell (i.e., a fiber-reinforced resin composite) made of pressure-resistant fiber-reinforced plastics (FRP) that is provided so as to cover the inner shell. Specifically, Patent Document 2 describes that the inner shell is made of polyethylene resin, polypropylene resin, polyamide resin, etc. from the viewpoint of gas barrier properties, and the outer shell is made of fiber-reinforced plastic from the viewpoint of pressure resistance and weight reduction of the gas cylinder. In addition, examples of resins used for the fiber-reinforced plastic of the outer shell include thermosetting resin, polyamide resin, etc.

[0005] Also, ethylene-vinyl alcohol copolymer resins are known as resins with excellent gas barrier properties. Ethylene-vinyl alcohol copolymer resins have the property of being difficult to pass through many gases such as hydrogen, nitrogen, and oxygen. Therefore, ethylene-vinyl alcohol copolymer resin films are widely used in packaging containers for food, medicines, cosmetics, agricultural products, industrial products, and the like, as well as gasoline tanks for automobiles. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-118381 [Patent Document 2] Japanese Patent Application Publication No. 8-219391 Summary of the Invention [Problem to be solved by the invention]

[0007] As mentioned above, ethylene-vinyl alcohol copolymer resin is widely known. However, no fiber-reinforced resin sheet (or prepreg), which is an intermediate material using ethylene-vinyl alcohol copolymer resin as a matrix resin, has been reported. This is thought to be because polyamide resin is very often used when a fiber-reinforced resin sheet is molded using a thermoplastic resin as a matrix resin. Specifically, polyamide resin is inferior to thermosetting resin, but has high strength (e.g., tensile strength, bending strength, etc.) and heat resistance compared to other thermoplastic resins. On the other hand, ethylene-vinyl alcohol copolymer resin is remarkably excellent in flexibility and elasticity, and is widely used for the manufacture of resin molded products that require such properties. Therefore, many resin molded products that require both excellent gas barrier properties and high strength are generally composed of a two-layer structure of a layer made of a resin having gas barrier properties and a layer made of a fiber-reinforced resin composite material containing a polyamide resin or a thermosetting resin (see, for example, Patent Document 2).

[0008] For these reasons, it would be preferable to have a fiber-reinforced resin sheet as an intermediate material that can impart excellent gas barrier properties and high strength to the final resin molded product without being configured with a two-layer structure made of different resins. In addition, it is more preferable that the fiber-reinforced resin sheet also has good moldability so that it can be applied to resin molded products of various shapes.

[0009] Therefore, an object of the present invention is to provide a fiber-reinforced resin sheet which can provide a fiber-reinforced resin composite material having excellent gas barrier properties and high strength, and which has good moldability. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention includes the following preferred embodiments.

[0011] A fiber-reinforced resin sheet according to a first aspect of the present invention includes an ethylene-vinyl alcohol copolymer resin film having a thickness of 10 μm or more and 50 μm or less, and a plurality of reinforcing fibers laminated to the ethylene-vinyl alcohol copolymer resin film with the fiber directions oriented in the same direction, The volume fraction Vf of the reinforcing fibers is 20% or more and 70% or less, and The thickness is 20 μm or more and 80 μm or less.

[0012] A fiber reinforced resin chopped material according to a second aspect of the present invention is obtained by cutting the fiber reinforced resin sheet according to the first aspect into rectangles having short sides each having a length of 2 mm or more and 20 mm or less and a long side each having a length of 10 mm or more and 40 mm or less.

[0013] A fiber reinforced resin composite material according to a third aspect of the present invention includes a plurality of fiber reinforced resin sheets according to the first aspect, The plurality of fiber-reinforced resin sheets are laminated in the thickness direction with the fiber directions of the reinforcing fibers being in the same direction or having an angular difference in a two-dimensional plane.

[0014] Alternatively, a fiber reinforced resin composite material according to a third aspect of the present invention includes a plurality of fiber reinforced resin chopped materials according to the second aspect, The plurality of fiber-reinforced resin chopped materials are laminated in the thickness direction.

[0015] The fiber-reinforced resin composite according to the third aspect further comprises one or more carrier sheets, The carrier sheet preferably supports the stacked fiber-reinforced resin chopped materials on one or both surfaces thereof.

[0016] A resin molded product according to a fourth aspect of the present invention includes the fiber reinforced resin composite material according to the third aspect. Effect of the Invention

[0017] According to the present invention, a fiber-reinforced resin composite material having excellent gas barrier properties and high strength can be obtained, and a fiber-reinforced resin sheet having good moldability can be provided. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view of a laminated chopped sheet, which is an example of a fiber-reinforced resin composite material in this embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a laminated chopped sheet including a carrier sheet, which is an example of the fiber reinforced resin composite material in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present inventors have studied a fiber-reinforced resin sheet as an intermediate material that can obtain a fiber-reinforced resin composite having excellent gas barrier properties (particularly gas barrier properties against hydrogen gas) and high strength, and has good moldability. Therefore, the present inventors first assumed the use of an ethylene-vinyl alcohol copolymer resin with excellent gas barrier properties as a resin matrix in the development of a fiber-reinforced resin sheet that can achieve all of these effects. Here, generally, the greater the volume fraction Vf of the reinforcing fibers in a fiber-reinforced resin composite (or fiber-reinforced resin sheet), the greater the strength of the fiber-reinforced resin composite or its resin molded product. However, when the amount of reinforcing fibers impregnated into the resin matrix during the production of a fiber-reinforced resin sheet, which is an intermediate material, is excessively increased, the sheet becomes thick and its moldability is reduced. In addition, when the thickness of the ethylene-vinyl alcohol copolymer resin film is reduced in order to make the sheet thinner, it is also considered that the gas barrier properties of the fiber-reinforced resin composite and its resin molded product produced from the sheet are inferior. Furthermore, it is predicted that the value of the volume fraction Vf of the reinforcing fibers directly or indirectly affects the gas barrier properties of the fiber-reinforced resin composite and the resin molded product. Thus, it is assumed that it is difficult to make the moldability of the fiber-reinforced resin sheet as an intermediate material, and the gas barrier properties and strength of the fiber-reinforced resin composite and the resin molded product obtained by using the sheet all favorable.

[0020] However, as a result of intensive research conducted by the present inventors, it was found that a fiber-reinforced resin sheet as described above can be provided by selecting an ethylene-vinyl alcohol copolymer resin as a thermoplastic resin, constructing a fiber-reinforced resin sheet having a predetermined structure, and appropriately adjusting the thickness of the resin film, the volume content Vf of the reinforcing fibers, and the thickness of the sheet within predetermined ranges.

[0021] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. Note that the scope of the present invention is not limited to the embodiment described here, and various modifications can be made without departing from the spirit of the present invention.

[0022] <Fiber reinforced resin sheet> 1. Composition of fiber reinforced resin sheet First, the configuration of the fiber reinforced resin sheet in this embodiment will be described.

[0023] The fiber reinforced resin sheet in this embodiment includes an ethylene-vinyl alcohol copolymer resin film and a plurality of reinforcing fibers laminated on the ethylene-vinyl alcohol copolymer resin film. The plurality of reinforcing fibers are laminated on the ethylene-vinyl alcohol copolymer resin film with their fiber directions oriented in the same direction. Specifically, the plurality of reinforcing fibers can be laminated on the ethylene-vinyl alcohol copolymer resin film with their fiber directions being approximately parallel to the longitudinal direction of the fiber reinforced resin sheet and oriented in the same direction.

[0024] Here, in this specification, "the reinforcing fibers are laminated on the ethylene-vinyl alcohol copolymer resin film" includes the meanings of "the reinforcing fibers are laminated after being fused to the ethylene-vinyl alcohol copolymer resin film at least in part of each reinforcing fiber", "the reinforcing fibers are laminated after being attached to the ethylene-vinyl alcohol copolymer resin film at least in part of each reinforcing fiber", "the reinforcing fibers are laminated after being pressed to the ethylene-vinyl alcohol copolymer resin film at least in part of each reinforcing fiber", and "the reinforcing fibers are impregnated from the surface to the inside of the ethylene-vinyl alcohol copolymer resin film in about half of each reinforcing fiber". The specific meaning of such "lamination" varies depending on the physical property values ​​and shape of the ethylene-vinyl alcohol copolymer resin film, the type of treatment performed for lamination, and the conditions thereof. In other words, "lamination" in this specification means that heating, cooling and / or pressure treatment may be performed as necessary during "lamination".

[0025] Hereinafter, each component included in the fiber reinforced resin sheet will be described.

[0026] [Ethylene-vinyl alcohol copolymer resin film] The ethylene-vinyl alcohol copolymer resin film is a film containing an ethylene-vinyl alcohol copolymer resin. Furthermore, if necessary, the ethylene-vinyl alcohol copolymer resin film may contain other thermoplastic resins, other additives, and the like in addition to the ethylene-vinyl alcohol copolymer resin.

[0027] Each component contained in the ethylene-vinyl alcohol copolymer resin film will be described below.

[0028] (Ethylene-vinyl alcohol copolymer resin) The ethylene-vinyl alcohol copolymer resin is a resin consisting of a copolymer containing an ethylene unit and a vinyl alcohol unit. The ethylene-vinyl alcohol copolymer resin can be produced by any method known to those skilled in the art. For example, an ethylene-vinyl ester copolymer resin can be obtained by copolymerizing ethylene and a vinyl ester to obtain an ethylene-vinyl ester copolymer resin, and then saponifying the obtained copolymer resin using an alkali catalyst or the like to obtain an ethylene-vinyl alcohol copolymer resin. As the vinyl ester, a fatty acid vinyl ester such as vinyl acetate, vinyl propionate, or vinyl pivalate can be used. Of these, vinyl acetate is preferred.

[0029] The ethylene-vinyl alcohol copolymer resin may contain copolymerization components other than ethylene and vinyl alcohol, so long as the effects of the gas barrier property, strength, and moldability in this embodiment are not impaired. Examples of such other copolymerization components include units derived from vinylsilane compounds. Examples of units derived from vinylsilane compounds include units derived from vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxy-ethoxy)silane, and γ-methacryloxypropylmethoxysilane. Of these, it is preferable to use units derived from vinyltrimethoxysilane or vinyltriethoxysilane.

[0030] Furthermore, the ethylene-vinyl alcohol copolymer resin may contain, as other copolymerization components, units derived from α-olefins such as propylene and butene, unsaturated carboxylic acids such as (meth)acrylic acid and methyl (meth)acrylate, or esters thereof, and vinylpyrrolidone such as N-vinylpyrrolidone. The content of copolymerization components other than ethylene units and vinyl alcohol units in the ethylene-vinyl alcohol copolymer resin is preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 1 mol % or less.

[0031] The ethylene unit content of the ethylene-vinyl alcohol copolymer resin is preferably 18 mol% to 50 mol%. When the ethylene unit content is 18 mol% or more, the bending resistance of the obtained film can be improved. The ethylene unit content is more preferably 20 mol% or more, and even more preferably 25 mol% or more. On the other hand, when the ethylene unit content is 50 mol% or less, the gas barrier property of the film can be further improved. The ethylene unit content is more preferably 45 mol% or less, and even more preferably 40 mol% or less.

[0032] The saponification degree of the ethylene-vinyl alcohol copolymer resin is preferably 90 mol% or more. When the saponification degree is 90 mol% or more, the gas barrier property of the film can be further improved. The saponification degree is more preferably 95 mol% or more, and even more preferably 99 mol% or more. The ethylene unit content and the saponification degree can be measured by any method known to those skilled in the art, for example, 1 It can be determined by H-NMR measurement.

[0033] The melt flow rate of the ethylene-vinyl alcohol copolymer resin (measured at a temperature of 210° C. and a load of 2.16 kg) is preferably 0.1 g / 10 min to 200 g / 10 min. When the MFR of the ethylene-vinyl alcohol copolymer resin is in such a range, the melt moldability is good, and the film can be formed well. The melt flow rate of the ethylene-vinyl alcohol copolymer resin is more preferably 0.5 g / 10 min or more, and even more preferably 1 g / 10 min or more. The melt flow rate of the ethylene-vinyl alcohol copolymer resin is more preferably 50 g / 10 min or less, even more preferably 30 g / 10 min or less, and particularly preferably 15 g / 10 min or less. In this specification, the melt flow rate is a value measured in accordance with JIS K 7210:1999.

[0034] The melting point of the ethylene-vinyl alcohol copolymer resin is preferably 100°C to 230°C. When the melting point of the ethylene-vinyl alcohol copolymer resin is 100°C or higher, the gas barrier property can be reliably imparted to the film after molding. When the melting point of the ethylene-vinyl alcohol copolymer resin is 230°C or lower, the film can be well formed without deteriorating the melt moldability and thermal stability. In this specification, the melting point of the ethylene-vinyl alcohol copolymer resin is a value measured based on JIS K7121:2012.

[0035] As such an ethylene-vinyl alcohol copolymer resin, any commercially available product known to those skilled in the art may be used. Examples of commercially available ethylene-vinyl alcohol copolymer resins include "EVAL (registered trademark) F104B" manufactured by Kuraray Co., Ltd., "EVAL (registered trademark) E105B" manufactured by Kuraray Co., Ltd., "EVAL (registered trademark) F101A / B" manufactured by Kuraray Co., Ltd., "Soarlite" manufactured by Mitsubishi Chemical Corporation, and "Sonoar" manufactured by Mitsubishi Chemical Corporation.

[0036] (Other additives) The ethylene-vinyl alcohol copolymer resin film may contain any additive known to those skilled in the art as necessary, within a range that does not impair the effects of the gas barrier property, strength, and moldability in this embodiment. For example, antioxidants, light stabilizers, weather resistance improvers, etc. can be added to improve the storage stability of the ethylene-vinyl alcohol copolymer resin film and prevent discoloration or deterioration of the cured product.

[0037] Examples of other additives include thermosetting elastomers, thermoplastic elastomers, flame retardants (e.g., phosphorus-containing polyamide resins, red phosphorus, phosphazene compounds, phosphates, phosphoric acid esters, etc.), silicone oils, wetting and dispersing agents, antifoaming agents, defoaming agents, natural waxes, synthetic waxes, metal salts of linear fatty acids, acid amides, esters, release agents such as paraffins, powders such as crystalline silica, fused silica, calcium silicate, alumina, calcium carbonate, talc, barium sulfate, metal oxides, metal hydroxides, inorganic fillers such as glass fibers, carbon nanotubes, and fullerenes, organic fillers such as carbon fibers and cellulose nanofibers, colorants such as red iron oxide, silane coupling agents, conductive materials, slip agents, leveling agents, polymerization inhibitors such as hydroquinone monomethyl ether, ultraviolet absorbers, etc. These additives can be used alone or in combination of two or more.

[0038] The method for producing the ethylene-vinyl alcohol copolymer resin film is not particularly limited, and the film can be produced by any method known to those skilled in the art. For example, roll coating, reverse coating, comma coating, knife coating, die coating, gravure coating, melt extrusion molding, solution casting, T-die method, calendar method, etc. can be mentioned. In addition, by using a coextrusion method or a lamination method, the thickness of the film can be increased, or resin films having different resin compositions can be laminated.

[0039] The thickness of the ethylene-vinyl alcohol copolymer resin film is 10 μm or more and 50 μm or less. By making the thickness of the ethylene-vinyl alcohol copolymer resin film 10 μm or more, when a fiber-reinforced resin sheet is molded so that the volume fraction Vf of the reinforcing fibers and the thickness of the sheet are within a predetermined range, a fiber-reinforced resin composite material having excellent gas barrier properties (particularly gas barrier properties against hydrogen gas) can be obtained. Furthermore, the shape of the fiber-reinforced resin sheet can be well maintained. By making the thickness of the ethylene-vinyl alcohol copolymer resin film 50 μm or less, when a fiber-reinforced resin sheet is molded so that the volume fraction Vf of the reinforcing fibers and the thickness of the sheet are within a predetermined range, the fiber-reinforced resin sheet has good moldability.

[0040] The thickness of the ethylene-vinyl alcohol copolymer resin film is preferably 15 μm or more, and preferably 30 μm or less, more preferably 25 μm or less, and further preferably 20 μm or less.

[0041] Such an ethylene-vinyl alcohol copolymer resin film is an intermediate material for producing the fiber reinforced resin sheet of this embodiment. A plurality of reinforcing fibers are laminated on one or both surfaces of the ethylene-vinyl alcohol copolymer resin film so that the fiber direction is oriented in the same direction, and the laminate is heated, cooled and / or pressurized. As a result, the fiber reinforced resin sheet of this embodiment can be obtained. From the viewpoint of obtaining higher strength and excellent handling during processing, it is preferable that a plurality of reinforcing fibers are laminated on both surfaces of the ethylene-vinyl alcohol copolymer resin film. Alternatively, the fiber reinforced resin sheet of this embodiment may include two or more ethylene-vinyl alcohol copolymer resin films, and a plurality of reinforcing fibers may be laminated on one ethylene-vinyl alcohol copolymer resin film, and another ethylene-vinyl alcohol copolymer resin film may be disposed on the surface of the resin film on which the plurality of reinforcing fibers are laminated. That is, the fiber reinforced resin sheet may be formed so that a plurality of reinforcing fibers are sandwiched between two or more ethylene-vinyl alcohol copolymer resin films.

[0042] [Multiple reinforcing fibers] The multiple reinforcing fibers are laminated on the ethylene-vinyl alcohol copolymer resin film with the fibers oriented in the same direction. The multiple reinforcing fibers laminated are multiple reinforcing fibers opened from a reinforcing fiber bundle.

[0043] In this specification, the phrase "a state in which the fiber directions of (a plurality of reinforcing fibers) are oriented in the same direction" refers to a state in which the fiber directions of the respective reinforcing fibers extend in substantially parallel directions.

[0044] By laminating a plurality of reinforcing fibers in this state on the ethylene-vinyl alcohol copolymer resin film (specifically on the surface of the ethylene-vinyl alcohol copolymer resin film), the fiber-reinforced resin sheet has good moldability, and a fiber-reinforced resin composite material having high strength can be obtained. Furthermore, by using a fiber-reinforced resin sheet having such a configuration as an intermediate material, a fiber-reinforced resin composite material having significantly superior gas barrier properties (particularly gas barrier properties against hydrogen gas) can be obtained compared to a configuration consisting of only an ethylene-vinyl alcohol copolymer resin film.

[0045] The material of the reinforcing fiber is not particularly limited, but may be appropriately selected from any fiber known to those skilled in the art as a reinforcing fiber constituting a fiber-reinforced resin sheet according to the application. Specific examples include various fibers such as carbon fiber, aramid fiber, glass fiber, boron fiber, alumina fiber, silicon nitride fiber, and basalt fiber. Among these, from the viewpoint of specific strength and specific elasticity, carbon fiber, aramid fiber, glass fiber, boron fiber, alumina fiber, or silicon nitride fiber is preferable. Furthermore, among these, from the viewpoint of improving the strength and corrosion resistance of a resin molded product manufactured using a fiber-reinforced resin sheet, carbon fiber is more preferable. The carbon fiber is more preferably a PAN (polyacrylonitrile)-based carbon fiber, which has particularly high strength. When carbon fiber is used as the reinforcing fiber, it may be surface-treated with a metal. In addition, the reinforcing fibers opened from these reinforcing fiber bundles can be used in one or more appropriate combinations as long as they are oriented in the same direction.

[0046] 2. Physical properties of fiber-reinforced resin sheets Next, the physical properties of the fiber reinforced resin sheet in this embodiment will be described.

[0047] In the fiber reinforced resin sheet of this embodiment, the volume fraction Vf of the reinforcing fibers in the fiber reinforced resin sheet is 20% or more and 70% or less. By making the volume fraction Vf of the reinforcing fibers 20% or more, the fiber reinforced resin sheet is sufficiently reinforced by the reinforcing fibers, and a fiber reinforced resin composite material having high strength (particularly, tensile strength and bending strength) can be obtained. By making the volume fraction Vf of the reinforcing fibers 70% or less, when the fiber reinforced resin sheet is molded so that the thickness of the resin film and sheet is within a predetermined range, the fiber reinforced resin sheet has good moldability, and a fiber reinforced resin composite material having excellent gas barrier properties (particularly gas barrier properties against hydrogen gas) can be obtained.

[0048] The volume fraction Vf of the reinforcing fibers is preferably 30% or more, more preferably 35% or more, even more preferably 40% or more, and particularly preferably 45% or more. The volume fraction Vf of the reinforcing fibers is preferably 65% ​​or less, more preferably 60% or less, even more preferably 55% or less, and particularly preferably 50% or less.

[0049] The volume fraction Vf of the reinforcing fibers can be adjusted within the above range by appropriately controlling not only the type and thickness of the reinforcing fibers, the fiber width in which the reinforcing fibers are oriented, the thickness of the film, etc., but also the temperature and pressure applied during the production of the fiber-reinforced resin sheet. In this specification, the volume fraction Vf of the reinforcing fibers is a value measured by a combustion method, as in the examples described later.

[0050] The thickness of the fiber reinforced resin sheet in this embodiment is 20 μm or more and 80 μm or less. The thickness of the fiber reinforced resin sheet is preferably 25 μm or more, more preferably 30 μm or more. The thickness of the fiber reinforced resin sheet is preferably 70 μm or less, more preferably 60 μm or less, and even more preferably 50 μm or less.

[0051] When the volume fraction Vf of the resin film and the reinforcing fibers is set within a predetermined range and the thickness of the sheet is as thin as possible within the above range, the resin film and the reinforcing fibers are laminated after being fused to each other in most parts. As a result, when a fiber-reinforced resin composite material is formed using the fiber-reinforced resin sheet, the strength of the reinforcing fibers can be fully exerted. In addition, when stress is applied to the fiber-reinforced resin composite material obtained from the fiber-reinforced resin sheet, delamination is unlikely to occur and the fatigue properties are also excellent. Furthermore, the moldability of the fiber-reinforced resin sheet is more excellent.

[0052] The thickness of the fiber-reinforced resin sheet is also affected by the thickness of the ethylene-vinyl alcohol copolymer resin film, but can be adjusted within the above range by appropriately controlling the temperature, pressure, etc. applied during the production of the fiber-reinforced resin sheet.

[0053] According to the fiber reinforced resin sheet of this embodiment, a fiber reinforced resin composite material having not only excellent gas barrier properties (particularly gas barrier properties against hydrogen gas) but also excellent reinforcing effect and fatigue resistance properties can be obtained. Furthermore, since the fiber reinforced resin sheet is relatively thin, it has good moldability. Therefore, the fiber reinforced resin sheet of this embodiment is preferably used as a material for manufacturing a resin molded product that needs to block or shield gas, particularly hydrogen gas, and also requires high strength. Furthermore, according to the fiber reinforced resin composite sheet of this embodiment, a plurality of fiber reinforced resin sheets can be laminated while minimizing voids to mold various shapes at high density. Therefore, it is possible to finally manufacture various types and shapes of resin molded products.

[0054] <Fiber reinforced resin chopped material> The fiber reinforced resin chopped material in this embodiment is obtained by chopping the fiber reinforced resin sheet in the above embodiment into rectangles with short sides of 2 mm to 20 mm and long sides of 10 mm to 40 mm (or is formed by chopping into rectangles). That is, like the fiber reinforced resin sheet in the above embodiment, the fiber reinforced resin chopped material includes an ethylene-vinyl alcohol copolymer resin film and a plurality of reinforcing fibers laminated on the ethylene-vinyl alcohol copolymer resin film with the fibers oriented in the same direction.

[0055] The fiber reinforced resin chopped material (hereinafter also simply referred to as "chopped material") can be suitably used for producing a fiber reinforced resin composite material described in an embodiment below.

[0056] As described above, in the fiber reinforced resin sheet, the multiple reinforcing fibers can be laminated on the ethylene-vinyl alcohol copolymer resin film with the fiber direction being approximately parallel to the longitudinal direction of the fiber reinforced resin sheet and oriented in the same direction. Therefore, in the chopped material obtained by chopping the fiber reinforced resin sheet, the multiple reinforcing fibers can be laminated on the resin film with the fiber direction being approximately parallel to the longitudinal direction (direction of the long side) of the chopped material and oriented in the same direction.

[0057] The larger the size of the chopped material, the stronger the fiber-reinforced resin composite material or resin molded product can be produced, but the lower the formability. On the other hand, the smaller the size of the chopped material, the better the formability, and the more flexible the shape of the fiber-reinforced resin composite material or resin molded product can be produced. However, in this case, the strength of the resin molded product, etc. is reduced. The size of the chopped material may be appropriately adjusted according to the application of the resin molded product, taking into consideration the balance between formability and mechanical properties due to such size.

[0058] The length of the short side of the chopped material is preferably 2 mm or more, more preferably 3 mm or more, even more preferably 4 mm or more, and particularly preferably 5 mm or more. The length of the short side of the chopped material is preferably 30 mm or less, more preferably 20 mm or less, even more preferably 15 mm or less, and particularly preferably 10 mm or less. The length of the long side of the chopped material is preferably 5 mm or more, more preferably 10 mm or more, even more preferably 15 mm or more, and particularly preferably 20 mm or more. The length of the long side of the chopped material is preferably 50 mm or less, more preferably 40 mm or less, even more preferably 30 mm or less, and particularly preferably 25 mm or less.

[0059] The thickness of the chopped material is the same as that of the fiber-reinforced resin sheet in the above embodiment, and is 20 μm or more and 80 μm or less. The preferred thickness is also the same as that of the fiber-reinforced resin sheet in the above embodiment. That is, because of its thinness and small size, the chopped material in this embodiment can be laminated in multiple sheets while minimizing voids. In other words, by using the chopped material in this embodiment, the density can be increased, and ultimately, a resin molded product having remarkably excellent strength and excellent gas barrier properties (especially gas barrier properties against hydrogen gas) and a shape with a higher degree of freedom can be manufactured.

[0060] <Fiber reinforced resin composite material> There are two specific embodiments of the fiber reinforced resin composite material, which will be described in detail below.

[0061] The fiber reinforced resin composite material in the first embodiment includes a plurality of the fiber reinforced resin sheets in the above-mentioned embodiment, and the plurality of fiber reinforced resin sheets are laminated in the thickness direction. As described above, the fiber reinforced resin composite material in the first embodiment has excellent gas barrier properties (particularly gas barrier properties against hydrogen gas) and high strength.

[0062] Here, in this specification, "fiber reinforced resin sheets (or fiber reinforced resin chopped materials) are laminated" includes the meanings of "fiber reinforced resin sheets (or fiber reinforced resin chopped materials) are laminated after being fixed at least in part", "fiber reinforced resin sheets (or fiber reinforced resin chopped materials) are laminated after being bonded at least in part", "fiber reinforced resin sheets (or fiber reinforced resin chopped materials) are laminated after being fused at least in part", "fiber reinforced resin sheets (or fiber reinforced resin chopped materials) are laminated after being attached at least in part", and "fiber reinforced resin sheets (or fiber reinforced resin chopped materials) are laminated after being pressed at least in part". The specific meaning of such "lamination of fiber reinforced resin sheets (or fiber reinforced resin chopped materials)" varies depending on the physical property values ​​and shape of the fiber reinforced resin sheets (or fiber reinforced resin chopped materials), the type of processing performed for lamination, and the conditions thereof. In other words, "lamination of fiber-reinforced resin sheets (or fiber-reinforced resin chopped material)" in this specification means that heating, cooling and / or pressure treatment may be applied as necessary when "laminating fiber-reinforced resin sheets or fiber-reinforced resin chopped material."

[0063] The multiple fiber reinforced resin sheets to be laminated may be cut into pieces or the like as necessary to match the shape of the desired fiber reinforced resin composite material, and then laminated. The number of fiber reinforced resin sheets to be laminated is not particularly limited, and may be appropriately set according to the size of the desired fiber reinforced resin composite material, etc.

[0064] A plurality of fiber-reinforced resin sheets may be stacked in the thickness direction with the fiber direction of the reinforcing fibers being in any direction. For example, a plurality of fiber-reinforced resin sheets may be stacked in the thickness direction with the fiber direction of the reinforcing fibers being in the same direction. Alternatively, a plurality of fiber-reinforced resin sheets may be stacked in the thickness direction with the fiber direction of the reinforcing fibers having an angle difference in a two-dimensional plane.

[0065] As an example of the latter, a plurality of fiber-reinforced resin sheets may be laminated in the thickness direction so that the fiber directions of the reinforcing fibers are aligned in four axial directions with an angle difference of 45°. In other words, a plurality of fiber-reinforced resin sheets may be laminated in the thickness direction so that the fiber directions of the reinforcing fibers are aligned in four axial directions of 0°, 45°, -45°, and 90° in a two-dimensional plane. By laminating the fiber-reinforced resin sheets in such a fiber direction, the tensile strength and bending strength along each fiber direction can be improved, and the strength of the fiber-reinforced resin composite material as a whole can be effectively improved. In this case, it is preferable that the fiber-reinforced resin sheets are laminated in the thickness direction by 4×n sheets (n is an integer of 1 or more). Alternatively, a plurality of fiber-reinforced resin sheets may be laminated in the thickness direction in a state in which the fiber directions of the reinforcing fibers are two-dimensionally random (quasi-isotropic).

[0066] The fiber reinforced resin composite material in the second embodiment includes a plurality of the fiber reinforced resin chopped materials in the above-mentioned embodiment, and the plurality of fiber reinforced resin chopped materials are laminated in the thickness direction. As described above, the fiber reinforced resin composite material in the second embodiment also has excellent gas barrier properties (especially gas barrier properties against hydrogen gas) and high strength.

[0067] In such a fiber-reinforced resin composite, a plurality of chopped materials may be laminated in the thickness direction with the fiber direction of the reinforcing fibers being in any direction. It is preferable that the plurality of chopped materials are laminated in a state where the fiber direction of the reinforcing fibers is two-dimensionally random (quasi-isotropic).

[0068] FIG. 1 shows a schematic cross-sectional view of a laminated chopped sheet, which is an example of a fiber-reinforced resin composite. As shown in FIG. 1, the laminated chopped sheet CS is formed by stacking a plurality of chopped materials C in the thickness direction. Specifically, the laminated chopped sheet CS is formed by integrating a plurality of stacked chopped materials C. t is the thickness of the laminated chopped sheet CS. The thickness t of the laminated chopped sheet CS can be controlled by appropriately adjusting the number of stacked chopped materials C.

[0069] Alternatively, the fiber reinforced resin composite of the second embodiment may further include one or more carrier sheets supporting the stacked chopped material on one or both sides thereof.

[0070] FIG. 2 shows a schematic cross-sectional view of a laminated chopped sheet including a carrier sheet, which is an example of a fiber-reinforced resin composite. As shown in FIG. 2, a plurality of chopped materials C are stacked in the thickness direction to form a laminate, and the laminate is supported on the upper surface of a carrier sheet R. Specifically, the laminated chopped sheet CS is configured by integrating a plurality of stacked chopped materials C with each other, and integrating the carrier sheet R with a large number of chopped materials C on its upper surface. The thickness t of the laminated chopped sheet CS including the carrier sheet R can be controlled by appropriately adjusting the thickness of the carrier sheet R and the number of stacked chopped materials C.

[0071] In FIG. 2, the case where the chopped material C is laminated only on the upper surface of the carrier sheet R to produce the laminated chopped sheet CS is illustrated, but the chopped material C may be laminated on both sides of the carrier sheet R. In this case, the operation of laminating the chopped material C on the carrier sheet R (that is, the operation of randomly arranging the chopped material C on the carrier sheet R and subjecting it to heating and pressure treatment) may be performed on the upper and lower surfaces of the carrier sheet R in order. That is, after laminating the chopped material C on the upper surface of the carrier sheet R, the carrier sheet R is turned over so that the lower surface of the carrier sheet R faces up. Then, the operation of laminating the chopped material C in this state is repeated in the same manner. As a result, a laminated chopped sheet in which the chopped material C is laminated on both sides of the carrier sheet R can be produced.

[0072] <Resin molded products> The resin molded product in this embodiment includes the fiber reinforced resin composite material in the above-described embodiment.

[0073] The resin molded product may be any resin molded product of any shape that can be manufactured using the fiber-reinforced resin composite material in the above-mentioned embodiment by any molding method known to those skilled in the art. Examples of the resin molded product include gas sealing members, gas interrupting members, and gas shielding members in general industrial applications, sports applications, aerospace applications, etc. Specifically, examples of the resin molded product include gas sealing members used in various vehicles such as automobiles, motorcycles, and railway cars, and moving bodies such as ships, gas interrupting members and gas shielding members applied to foods, medicines, industrial products, etc. Among these, the resin molded product is preferably a pressure-resistant container such as a gas cylinder, a gas tank, or an air tank, which requires excellent gas barrier properties (especially gas barrier properties against hydrogen gas) and strength, a highly durable protective bag, a protective sheath layer of a pressure-resistant hose, a protective sheath layer of a submarine cable, and the like. In particular, while pressure-resistant containers mounted on conventional automobiles and the like are generally formed in a two-layer structure using two or more types of resin materials (for example, see Patent Document 2), according to this embodiment, the pressure-resistant container can be formed in a single-layer structure using one type of resin material. In other words, since the resin molded product (for example, pressure-resistant container) in this embodiment uses the fiber-reinforced resin sheet of the above-mentioned embodiment as an intermediate material, even if it is formed in a single-layer structure using this sheet as a material, the resin molded product has excellent gas barrier properties and high strength.

[0074] The manufacturing method of the resin molded product is not particularly limited, but for example, the following manufacturing method can be mentioned. First, the laminated chopped sheet described in the above embodiment is cut into a plate shape of a predetermined size, and a plurality of sheets are prepared. Next, the prepared laminated chopped sheets are stacked in the thickness direction and placed in a mold such as a heat press. After that, the stacked laminated chopped sheets are heated and / or pressed, and cooled as necessary. By such a method, a resin molded product can be manufactured.

[0075] According to the above-mentioned manufacturing method, a resin molded product having particularly excellent gas barrier properties (particularly gas barrier properties against hydrogen gas) and high strength can be obtained. Specifically, as described above, the laminated chopped sheet can be laminated in a state where the fiber directions of the reinforcing fibers are two-dimensionally random (quasi-isotropic). Therefore, when the laminated chopped sheet is pressed, the possibility that the reinforcing fibers will be chopped can be reduced, and the flow of the resin during press processing can be promoted to increase the degree of freedom in the shape of the resin molded product. This allows the reinforcing effect of the reinforcing fibers to be exerted isotropically, and resin molded products of various shapes can be molded without any problems. EXAMPLES

[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0077] In this embodiment, the volume fraction Vf of the reinforcing fiber was measured by a combustion method. In addition, in this embodiment, the thickness of the ethylene-vinyl alcohol copolymer resin film and the thickness of the fiber-reinforced resin sheet were measured using a micrometer manufactured by Mitutoyo Corporation.

[0078] In this example, the type of resin in the resin film, the thickness of the film, the volume fraction Vf of the reinforcing fiber, and the thickness of the fiber-reinforced resin sheet were changed to produce fiber-reinforced resin sheets of each example and each comparative example. In addition, each of the produced fiber-reinforced resin sheets was cut out to obtain evaluation fiber-reinforced resin sheets used for evaluating moldability. Furthermore, each of the produced fiber-reinforced resin sheets was used to produce test pieces of fiber-reinforced resin composites used for measuring gas barrier properties and strength.

[0079] [Methods for producing fiber-reinforced resin sheets, fiber-reinforced resin composites, and test pieces thereof] First, the methods for producing the fiber reinforced resin sheets, fiber reinforced resin composite materials, and test pieces thereof in each of the examples and comparative examples will be described in detail below.

[0080] Example 1 To prepare a fiber-reinforced resin sheet, an ethylene-vinyl alcohol copolymer resin film was first prepared. Using an extrusion molding machine equipped with a T-die, pellets of an ethylene-vinyl alcohol copolymer resin (manufactured by Kuraray Co., Ltd., "EVAL (registered trademark) F104B", ethylene unit content 32 mol%) were molded into a film.

[0081] Using this ethylene-vinyl alcohol copolymer resin film and carbon fibers (manufactured by Toray Industries, Inc., "TORAYCA", grade: T-700 (PAN-based carbon fiber), fiber diameter: 7 μm, filament count: 12K, fineness: 800 tex) as reinforcing fibers, a fiber-reinforced resin sheet was produced while spreading the carbon fiber bundles. The obtained fiber-reinforced resin sheet has the spread carbon fiber bundles laminated on both sides of the ethylene-vinyl alcohol copolymer resin film.

[0082] The fiber-reinforced resin sheet thus obtained was cut into a size of 10 mm (length in the minor axis direction) x 3 m (length in the major axis direction) to obtain a fiber-reinforced resin sheet for evaluation of moldability.

[0083] A test piece of the fiber reinforced resin composite for measuring the gas barrier property was prepared as follows. First, the obtained fiber reinforced resin sheet was cut into a size of 295 mm (length in the short axis direction) × 295 mm (length in the long axis direction). Next, 12 sheets of the cut out sheets were stacked so that the carbon fibers were arranged in four axial directions with an angle difference of 45°. Next, the stacked sheets were pressurized while being heated, and then pressed while being cooled. Then, a fiber reinforced resin composite having a thickness of 0.3 mm was taken out of the mold, and this fiber reinforced resin composite was cut into a size of diameter Φ60 mm × thickness 0.3 mm.

[0084] The test pieces of the fiber-reinforced resin composite for measuring the tensile strength and bending strength were prepared as follows. First, the obtained fiber-reinforced resin sheet was cut into a size of 295 mm (length in the short axis direction) x 295 mm (length in the long axis direction). Next, 96 sheets of the cut-out sheets were stacked so that the carbon fibers were aligned in four axial directions with an angle difference of 45°. Next, the stacked sheets were pressurized while being heated, and then pressed while being cooled. Then, a fiber-reinforced resin composite with a thickness of 2 mm was taken out of the mold, and this fiber-reinforced resin composite was cut into a size of 25 mm (length in the short axis direction) x 100 mm (length in the long axis direction) x 2 mm (thickness) and a size of 15 mm (length in the short axis direction) x 100 mm (length in the long axis direction) x 2 mm (thickness).

[0085] The thickness of the resin film, the volume fraction Vf of the carbon fibers in the fiber reinforced resin sheet, and the thickness of the fiber reinforced resin sheet in Example 1 are summarized in Table 1 below. In each Example and Comparative Example, the volume fraction Vf of the carbon fibers in the test piece of the fiber reinforced resin composite material is the same as the volume fraction Vf of the carbon fibers in the fiber reinforced resin sheet.

[0086] (Examples 2 to 5 and Comparative Examples 1 to 4) Fiber reinforced resin sheets were obtained by the same method as in Example 1, except that the thickness of the film, the volume fraction Vf of the reinforcing fibers, and the thickness of the fiber reinforced resin sheet were changed by varying the amounts of pellets and carbon fibers used. These physical properties in Examples 2 to 5 and Comparative Examples 1 to 4 are summarized in Table 1 below. Furthermore, the obtained fiber reinforced resin sheets were cut into the same size as the evaluation sheets in Example 1 to obtain fiber reinforced resin sheets for evaluating moldability.

[0087] Fiber-reinforced resin composite test pieces for measuring gas barrier properties having the same size as the test pieces of Example 1 were obtained by the same method as in Example 1 except that the number of laminated fiber-reinforced resin sheets was changed. Specifically, in Examples 2 to 5, the number of laminated fiber-reinforced resin sheets was 6, 6, 4, or 4, respectively. In Comparative Examples 1 to 4, the number of laminated fiber-reinforced resin sheets was 12, 12, 4, or 4, respectively.

[0088] Furthermore, test pieces of fiber reinforced resin composite materials for measuring tensile strength and bending strength having the same size as the test pieces of Example 1 were obtained by the same method as in Example 1 except that the number of laminated fiber reinforced resin sheets was changed. Specifically, in Examples 2 to 5, the number of laminated fiber reinforced resin sheets was 48, 48, 32, or 32, respectively. In Comparative Examples 1 to 4, the number of laminated fiber reinforced resin sheets was 96, 96, 32, or 32, respectively.

[0089] Comparative Example 5 In Comparative Example 5, a resin sheet consisting of only an ethylene-vinyl alcohol copolymer resin film was produced without laminating reinforcing fibers. Specifically, using an extruder equipped with a T-die, pellets of an ethylene-vinyl alcohol copolymer resin (manufactured by Kuraray Co., Ltd., "EVAL (registered trademark) F104B", ethylene unit content 32 mol%) were molded into a film having a thickness of 300 μm under a molding temperature condition of 230° C.

[0090] The obtained resin sheet consisting of only the resin film was cut into the same size as the evaluation sheet of Example 1 to obtain a resin sheet for evaluating moldability.

[0091] Furthermore, the resin sheet consisting of the obtained resin film alone was cut into a size of Φ60 mm in diameter×0.3 mm in thickness to obtain a test piece for measuring the gas barrier property.

[0092] A resin molded product consisting only of ethylene-vinyl alcohol copolymer resin was separately produced to have the same size as the test piece in Example 1, thereby obtaining test pieces of the resin molded product for measuring tensile strength and flexural strength.

[0093] Comparative Example 6 A fiber-reinforced resin sheet was obtained by the same method as in Example 1, except that the type of resin was polyamide 9T (manufactured by Kuraray, "Genestar" (registered trademark)) and the film thickness, the volume content Vf of the reinforcing fibers, and the thickness of the fiber-reinforced resin sheet were changed by varying the amount of pellets and carbon fibers used. These physical properties in Comparative Example 6 are summarized in Table 1 below. Furthermore, the obtained fiber-reinforced resin sheet was cut into the same size as the evaluation sheet in Example 1 to obtain a fiber-reinforced resin sheet for evaluation of moldability.

[0094] A test piece of a fiber-reinforced resin composite for measuring gas barrier properties having the same size as the test piece of Example 1 was obtained by the same method as in Example 1, except that the number of fiber-reinforced resin sheets to be laminated was six.

[0095] Furthermore, a test piece of a fiber-reinforced resin composite for measuring tensile strength and flexural strength having the same size as the test piece of Example 1 was obtained by the same method as in Example 1, except that the number of fiber-reinforced resin sheets to be laminated was 48.

[0096] Comparative Example 7 A fiber-reinforced resin sheet was obtained by the same method as in Example 1, except that the type of resin was polyamide 6 (manufactured by Mitsubishi Chemical Corporation, "Diamilon", grade: CZ (melting point Tm 225°C)) and the amount of pellets and carbon fibers used was varied to change the film thickness, the volume content Vf of the reinforcing fibers, and the thickness of the fiber-reinforced resin sheet. These physical properties in Comparative Example 7 are summarized in Table 1 below. Furthermore, the obtained fiber-reinforced resin sheet was cut into the same size as the evaluation sheet in Example 1 to obtain a fiber-reinforced resin sheet for evaluation of moldability.

[0097] A test piece of a fiber-reinforced resin composite for measuring gas barrier properties having the same size as the test piece of Example 1 was obtained by the same method as in Example 1, except that the number of fiber-reinforced resin sheets to be laminated was two.

[0098] Furthermore, a test piece of a fiber-reinforced resin composite for measuring tensile strength and flexural strength having the same size as the test piece of Example 1 was obtained by the same method as in Example 1, except that the number of fiber-reinforced resin sheets to be laminated was 16.

[0099] Next, the gas barrier properties, tensile strength, and bending strength of each of the cut test pieces of the fiber reinforced resin composite material were measured by the methods described below. Furthermore, the moldability of each of the cut fiber reinforced resin composite sheets was evaluated by the methods described below.

[0100] [Gas barrier property measurement] The gas barrier properties of the fiber-reinforced resin composite were measured by the following method. Specifically, a differential pressure gas chromatograph method conforming to JIS K 7126-1:2006 was applied to measure the hydrogen permeability coefficient of a test piece of fiber-reinforced resin composite with a diameter of Φ60 mm and a thickness of 0.3 mm. A differential pressure gas and vapor permeability measuring device (GTR-30XAD2, G2700T F-2 manufactured by GTR Tech Yanaco Technical Science Co., Ltd.) was used for the measurement. Hydrogen permeability coefficient (cc·20μm / (m 2 The hydrogen permeability coefficient was measured under conditions of 20°C, relative humidity 0°C, and 1 atm. The smaller the hydrogen permeability coefficient, the better the gas barrier properties. 2 If the gas barrier strength was less than 1.0 MPa (24 h atm), the fiber-reinforced resin composite was determined to have good gas barrier properties.

[0101] [Measurement of tensile strength (MPa)] The tensile strength of the fiber reinforced resin composite material was measured by the following method. Specifically, the tensile strength of a test piece of the fiber reinforced resin composite material measuring 25 mm (length in the minor axis direction) × 100 mm (length in the major axis direction) × 2 mm (thickness) was measured in accordance with JIS K 7164:2005. When the tensile strength of the fiber reinforced resin composite material was 400 MPa or more, it was determined that the material had sufficient tensile strength.

[0102] [Measurement of bending strength (MPa)] The bending strength of the fiber reinforced resin was measured by the following method. Specifically, the bending strength of a test piece of the fiber reinforced resin composite material measuring 15 mm (length in the minor axis direction) x 100 mm (length in the major axis direction) x 2 mm (thickness) was measured in accordance with the bending test method for four-point bending (method B) of carbon fiber reinforced plastics specified in JIS K 7074:1988. When the bending strength of the fiber reinforced resin composite material was 500 MPa or more, it was determined that it had sufficient bending strength.

[0103] [Evaluation of molding processability] The moldability of the fiber-reinforced resin sheet was evaluated by the following method. A fiber-reinforced resin sheet cut into a size of 10 mm (length in the minor axis direction) x 3 m (length in the major axis direction) was wrapped around a cylinder with a diameter of 30 cm, and the state of the fiber-reinforced resin sheet after wrapping was visually observed. The evaluation was divided into the following three stages. ⊚: The fiber-reinforced resin sheet was easily wrapped around the cylinder without generation of fluff or wrinkles. ◯: The fiber reinforced resin sheet is wrapped around the cylinder, but fuzz and wrinkles are generated. ×: The fiber reinforced resin sheet cannot be wrapped around the cylinder.

[0104] [result] The configurations, physical properties, etc. of the resin films, fiber-reinforced resin sheets, and fiber-reinforced resin composite materials in each of the Examples and Comparative Examples, as well as the measurement or evaluation results of the gas barrier properties, tensile strength, flexural strength, and molding processability, are summarized in the following Table 1. In Table 1, "EVOH" is an ethylene-vinyl alcohol copolymer resin, "PA9T" is polyamide 9T, and "PA6" is polyamide 6.

[0105] [Table 1]

[0106] [Consideration] (Examples 1 to 5) In Examples 1 to 5, the fiber reinforced resin sheets, which are intermediate materials, satisfy three requirements: the resin film thickness is 10 μm or more and 50 μm or less, the volume fraction Vf of the reinforcing fibers is 20% or more and 70% or less, and the thickness is 20 μm or more and 80 μm or less. As shown in Table 1 above, in Examples 1 to 5, the evaluation results of the gas barrier properties (gas permeability coefficient), tensile strength, bending strength, and molding processability were all good.

[0107] In particular, the test pieces of the fiber-reinforced resin composites of Examples 1 to 5 were significantly superior in tensile strength, flexural strength, and molding processability as well as in gas barrier properties compared to the resin molded product of Comparative Example 5 composed only of an ethylene-vinyl alcohol copolymer resin film.

[0108] In addition, the volume fraction Vf of the reinforcing fibers in Examples 1 to 3 is smaller than the volume fraction Vf of the reinforcing fibers in Comparative Example 1. Nevertheless, the fiber-reinforced resin composites in Examples 1 to 3 had higher tensile strength and bending strength than the fiber-reinforced resin composite in Comparative Example 1, which is the opposite of the results that would normally be expected. This is because the fiber-reinforced resin composites in Examples 1 to 3 are composed of multiple layers of fiber-reinforced resin sheets with good dispersion of the reinforcing fibers and resin, and it is assumed that the strength inherent to the reinforcing fibers was expressed. Furthermore, it is assumed that the fiber-reinforced resin composite in Comparative Example 1 had a resin film that was too thin, which caused quality variations and insufficient impregnation in some places, resulting in poor strength. It is considered that the dispersion of the reinforcing fibers and resin in the fiber-reinforced resin composite can be improved by appropriately adjusting the balance between the thickness of the resin film, the volume fraction Vf of the reinforcing fibers, and the thickness of the fiber-reinforced resin sheet.

[0109] Comparative Example 1 In Comparative Example 1, the impregnation of the reinforcing fibers of the fiber-reinforced resin sheet with the resin was poor, and a lot of fuzz was generated on the sheet. Therefore, in Comparative Example 1, the gas barrier property and molding processability were inferior to the results of Examples 1 to 5. This is considered to be because the resin film was too thin and the volume fraction Vf of the reinforcing fibers was too large.

[0110] Comparative Example 2 In Comparative Example 2, many gaps were generated between the reinforcing fibers and the resin of the fiber reinforced resin sheet, and many wrinkles were generated on the sheet. Therefore, in Comparative Example 2, the gas barrier property and molding processability were inferior to the results of Examples 1 to 5. This is thought to be because the resin film and the fiber reinforced resin sheet were too thin.

[0111] Comparative Example 3 The fiber reinforced resin composite material of Comparative Example 3 did not have sufficient tensile strength and bending strength. This is believed to be because the resin film was thick and the volume fraction Vf of the reinforcing fibers was small.

[0112] Comparative Example 4 The fiber reinforced resin sheet of Comparative Example 4 had no flexibility and could not be wound around a cylinder, and had poor moldability. This is believed to be because the resin film and the fiber reinforced resin sheet were too thick.

[0113] Comparative Example 5 The resin molded product of Comparative Example 5, in which no reinforcing fibers were laminated, was significantly inferior in gas barrier properties compared to the results of Examples 1 to 5. Furthermore, the tensile strength was also significantly inferior. Furthermore, since the resin molded product did not break, the bending strength could not be measured, and the strength was naturally inferior. In addition, regarding the molding processability, it was difficult to wrap the resin sheet around a cylinder. This is because, when no reinforcing fibers are laminated on the resin film, the resin sheet has excellent flexibility, but does not have sufficient stiffness required for wrapping the sheet.

[0114] Comparative Example 6 In Comparative Example 6, the gas barrier property was inferior to the results of Examples 1 to 5 (especially Example 3). This is believed to be because the resin used was polyamide 9T, which has a gas barrier property inferior to that of ethylene-vinyl alcohol copolymer resin.

[0115] Comparative Example 7 In Comparative Example 7, the gas barrier property was inferior to the results of Examples 1 to 5. This is believed to be because the type of resin used was polyamide 6, which has a gas barrier property inferior to that of ethylene-vinyl alcohol copolymer resin.

[0116] As described above, a fiber-reinforced resin sheet that satisfies the three requirements of a resin film thickness of 10 μm or more and 50 μm or less, a reinforcing fiber volume fraction Vf of 20% or more and 70% or less, and a thickness of 20 μm or more and 80 μm or less can produce a fiber-reinforced resin composite material that has excellent gas barrier properties and high strength (tensile strength and flexural strength), and also has good molding processability.

[0117] The embodiments and examples disclosed herein should be understood to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0118] C Chopped material CS laminated chopped sheet R Career Sheet

Claims

1. The present invention comprises an ethylene-vinyl alcohol copolymer resin film having a thickness of 10 μm or more and 50 μm or less, and a plurality of reinforcing fibers impregnated into the ethylene-vinyl alcohol copolymer resin film with the fiber directions oriented in the same direction, The volume fraction Vf of the reinforcing fibers is 21% or more and 53% or less, and A fiber reinforced resin sheet having a thickness of 20 μm or more and 80 μm or less.

2. A fiber reinforced resin chopped material obtained by cutting the fiber reinforced resin sheet according to claim 1 into a rectangle having a short side length of 2 mm or more and 20 mm or less and a long side length of 10 mm or more and 40 mm or less.

3. The chopped material according to claim 2 is a plurality of fiber reinforced resin chopped materials. A fiber reinforced resin composite material, in which the plurality of fiber reinforced resin chopped materials are laminated in the thickness direction.

4. further comprising one or more carrier sheets; The fiber reinforced resin composite material according to claim 3 , wherein the carrier sheet supports the stacked fiber reinforced resin chopped materials on one or both surfaces thereof.

Citation Information

Patent Citations

  • racket

    JP1992090772A

  • Manufacture of cfrp molded product

    JP1996118381A

  • Gas cylinder and manufacture thereof

    JP1996219391A

  • Manufacturing method of fiber reinforced thermoplastic resin ring

    JP2004122683A

  • Fiber-reinforced composite material, manufacturing method of the same, and manufacturing method of resin molding

    JP2021066081A